GONOCOCCAL INFECTIONS AND GENITAL MICROBIOTA DISORDERS IN GIRLS: CLINICAL FEATURES, DIAGNOSIS, AND PREVENTION (Eureka Journal of Education & Learning Technologies, 2026)
Sexually transmitted infections (STIs) are a significant public health concern affecting the reproductive health of women. This article analyzes gonococcal infections in girls and young women, specifically gonorrhea, gonoblennorrhea, and gonococcal proctitis, as well as genital microbiota disorders such as bacterial vaginosis, mycoplasmosis, and ureaplasmosis. The etiology, pathogenesis, clinical features, and preventive measures are reviewed. Modern diagnostic methods enable early detection of these infections. The results highlight the importance of timely diagnosis and treatment to preserve reproductive health.
Keywords: Gonorrhea, gonoblennorrhea, bacterial vaginosis, mycoplasmosis, ureaplasmosis, reproductive health, sexually transmitted infections.